Assessment of Cardiorespiratory Fitness without Exercise in Elderly Men with Chronic Cardiovascular and Metabolic Diseases - Maranhão Neto, Geraldo A.; de Leon, Antonio P.; Lira, Vitor A.; Farinatti, Paulo T. V. (Journal of Aging Research, 2012)
Low cardiorespiratory (CRF) is associated with health problems in elderly people, especially cardiovascular and metabolic disease. However, physical limitations in this population frequently preclude the application of aerobic tests. We developed a model to estimate CRF without aerobic testing in older men with chronic cardiovascular and metabolic diseases. Subjects aged from 60 to 91 years were randomly assigned into validation (n=67) and cross-validation (n=29) groups. A hierarchical linear regression model included age, self-reported fitness, and handgrip strength normalized to body weight (R2=0.79; SEE = 1.1 METs). The PRESS (predicted residual sum of squares) statistics revealed minimal shrinkage in relation to the original model and that predicted by the model and actual CRF correlated well in the cross-validation group (r=0.85). The area under curve (AUC) values suggested a good accuracy of the model to detect disability in the validation (0.876, 95% CI: 0.793–0.959) and cross-validation groups (0.826, 95% CI: 0.677–0.975). Our findings suggest that CRF can be reliably estimated without exercise test in unhealthy elderly men.